Perbaikan Pembukuan dan Pelatihan Penyusunan Laporan Keuangan Pada Lembaga POS PAUD Kenanga Kapanewon Nanggulan - Devi Shinta Nur Isnaeni Shinta; Endang Sri Utami (Rengganis Jurnal Pengabdian Masyarakat, 2023)
School financial management consists of various activities that organize school finances starting from planning, bookkeeping, spending, monitoring and accountability of school finances. In carrying out these activities, financial managers experience difficulties in the process due to the factor of knowledge that is not optimal. The purpose of this service is to introduce accounting knowledge to facilitate the preparation of financial reports, help improve the preparation of transactions into bookkeeping and provide assistance in preparing financial reports using Microsoft Excel at POS PAUD Kenanga institutions. This activity was carried out through three stages, namely the planning stage, the implementation stage and the evaluation stage. The planning stage begins with a location survey, preparing a permit to carry out activities, identifying problems then preparing training materials. The implementation stage is carried out by educating material about bookkeeping and simple financial reports then there is a question and answer session or discussion and providing assistance in preparing financial reports based on Microsoft Excel. The evaluation results of this training activity show that it has run well in accordance with the objectives set.